RELIGIOUS COMMUTERS: CONTEMPORARY BALINESE RELIGIOUS IDENTIFICATION IN A NORTHERN BALINESE TOWN - , Gde Dwitya Arief Metera; , Dr. Zainal Abidin Bagir ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Latest ethnographic accounts on contemporary Balinese religious identity look at the emergence of state-sponsored Agama Hindu promoted by Indonesian Hindu Council (PHDI) and proliferation of new religious movements like Sai Baba and Hare Krishna (Howe 2001, 2005). The emergence of state-sponsored Agama Hindu is seen largely as a response to the requirements set up by Indonesian Ministry of Religion in order for a religion to be formally recognized by the state (Forge 1980